User Management Dashboard Analysis on Bandwitdh Data Filtering Using the Hierachical Token Bucket Method (CASE STUDY: STATE VOCATIONAL SCHOOL 3 TANGERANG) - deni, Deni warsa (JUPIK : Jurnal Penelitian Ilmu komputer, 2023)
In filtering data, bandwidth will be something that is really needed for multi-service networks, because the variety of applications that can be served by a network will have an impact on the use of links in a particular network. This filtering certainly requires information related to the services that have been accessed by each user which is displayed on the user's dashboard. Bandwidth data filtering is really needed to regulate the available bandwidth so that each user can get bandwidth according to each user's needs. HTB (Hierarchical Token Bucket) is a queue grouping method that is useful for handling various types of traffic. Hierarchical Token Bucket (HTB) functions to regulate bandwidth distribution, the division is carried out hierarchically which is divided into classes so that it makes it easier to regulate bandwidth appropriately so that its use is maximized. The average download speed result after dividing the bandwidth using the HTB method on five test devices was 420.743 Kbps. The data transfer speed is in accordance with the standards set by the school, namely the minimum speed is 256 Kbps and the maximum speed is 8 Mbps. The application of the Per Connection Queue method which was carried out during the implementation of bandwidth management was proven to be able to increase the download time speed carried out by each individual. each client is on a private and public network significantly. apply Mikrotik OS as a network router because it has quite complete features and tools for both cable and wireless networks.